Immunogenomic Landscape in Breast Cancer Reveals Immunotherapeutically Relevant Gene Signatures - Wang, Tao; Li, Tianye; Li, Baiqing; Zhao, Jiahui; Li, Zhi; Sun, Mingyi; Li, Yan; Zhao, Yanjiao; Zhao, Shidi; He, Weiguang; Guo, Xiao; Ge, Rongjing; et al. (Frontiers in Immunology, 2022)
Breast cancer is characterized by high heterogeneity and aggressive behaviour and has low immunotherapeutic efficiency. Detailed immune stratification is a prerequisite for interpreting resistance to treatment and escape from immune control. Hence, the immune landscape of breast cancer needs further understanding. We systematically clustered breast cancer into six immune subtypes based on the mRNA expression patterns of immune signatures and comprehensively depicted their characteristics. The ITBscore was validated to be a superior predictor of the response to immunotherapy in cohorts from various datasets. Six distinct immune subtypes related to divergences in biological functions, signatures of immune or stromal cells, extent of the adaptive immune response, genomic events, and clinical prognostication were identified. These six subtypes were characterised as immunologically quiet, chemokine dominant, lymphocyte depleted, wounding dominant, innate immune dominan, and IFN-γ dominant and exhibited features of the tumour microenvironment (TME). The high ITBscore subgroup, characterized by a high proportion of M1 macrophages:M2 macrophages, an activated inflammatory response, and increased mutation burden (such as mutations in TP53, CDH1 and CENPE), indicated better immunotherapeutic benefits. A low proportion of tumour-infiltrating lymphocytes (TILs) and an inadequate response to immune treatment were associated with the low ITBscore subgroup, which was also associated with poor survival. Analyses of four cohorts treated with immune checkpoint inhibitors (ICIs) suggested that patients with a high ITBscore received significant therapeutic advantages and clinical benefits. Our work may facilitate the understanding of immune phenotypes in shaping different TME landscapes and guide precision immuno-oncology and immunotherapy strategies.